2021
DOI: 10.1177/10406387211057859
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-binding domain–based immunoassays for serosurveillance differentiate efficiently between SARS-CoV2–exposed and non-exposed farmed mink

Abstract: During the COVID-19 pandemic, infection of farmed mink has become not only an economic issue but also a widespread public health concern. International agencies have advised the use of strict molecular and serosurveillance methods for monitoring the SARS-CoV2 status on mink farms. We developed 2 ELISAs and a duplex protein microarray immunoassay (MI), all in a double-recognition format (DR), to detect SARS-CoV2 antibodies specific to the receptor-binding domain (RBD) of the spike protein and to the full-length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In contrast, a recent study in humans showed that LIPS using antibodies against the N protein is more sensitive than the detection of antibodies against the S protein and that N antibodies generally appear earlier than spike antibodies [23]. Sera analysed in [23] derived from patients with positive PCR results only indicated an early stage of infection, whereas samples from animals analysed by other authors and the ones included in this study were derived from a later stage of infection [ 13,18,27]. Diferent results obtained in [23] on humans compared to published data on animals might be due to diferent sera origins or that anti-N antibodies appear earlier but also decrease faster than anti-S antibodies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, a recent study in humans showed that LIPS using antibodies against the N protein is more sensitive than the detection of antibodies against the S protein and that N antibodies generally appear earlier than spike antibodies [23]. Sera analysed in [23] derived from patients with positive PCR results only indicated an early stage of infection, whereas samples from animals analysed by other authors and the ones included in this study were derived from a later stage of infection [ 13,18,27]. Diferent results obtained in [23] on humans compared to published data on animals might be due to diferent sera origins or that anti-N antibodies appear earlier but also decrease faster than anti-S antibodies.…”
Section: Discussionmentioning
confidence: 84%
“…S protein mediates attachment to host cells and virion entry and contains the receptor-binding domain (RBD) [12]. Te full N and S proteins and diferent S domains, including RBD, have been used as antigens for testing the SARS-CoV-2 humoral immune response [13]. In a previous report, we evaluated the use of LIPS assays targeting the S and N protein (LIPS-S and LIPS-N) on fve diferent animal species, including mink [7].…”
Section: Introductionmentioning
confidence: 99%